Green Collaboration: Agriculture and Fisheries Cultivation in Realizing Food Security - Fazira, Nurul; Fajriani , Annisa (Journal of Agro Complex Development Society, 2024)
Food security is an increasingly important global issue amidst population growth and climate change. This article examines the potential for collaboration between the agricultural and aquaculture sectors in realizing sustainable food security. This "Green Collaboration" approach aims to optimize resource use, increase productivity, and minimize environmental impact. Research methods include comprehensive literature studies and case study analyses from various countries that have implemented integrated agriculture-fisheries systems. The research results show that integration of these two sectors can increase the efficiency of land and water use, improve the nutrient cycle, and increase farmer income. Aquaponic systems, for example, combine fish farming with hydroponics, producing animal protein and vegetables simultaneously with more efficient use of water. Apart from that, the use of agricultural waste as fish feed and the use of fishery waste as organic fertilizer creates a more sustainable production cycle. Challenges in implementing this collaboration include the need for appropriate technology, training for farmers and cultivators, and supporting policies. In conclusion, the "Green Collaboration" between agriculture and aquaculture has significant potential to improve food security, production efficiency, and environmental sustainability.